Wireless 'mini' multichannel intraluminal impedance‐pH: what is the optimal design of a miniature wireless device?. Issue 5 (14th September 2012) - Heard, R.; Sharma, N.; Roberts, J.; Castell, D.; Pohl, D.
Summary Catheter‐based methods for multichannel intraluminal impedance‐pH monitoring are invasive and uncomfortable. The current alternative is a wireless system that clips to the esophageal mucosa, but which only measures pH. A shorter two‐site wireless sensor that detects impedance and pH, and can be clipped to the esophagus, would be desirable. This study compares sensor positions and separations to determine the optimal configuration of a two‐site wireless sensor. Records of 20 patients (10 on and 10 off proton pump inhibitor) who had ambulatory reflux testing with a multichannel intraluminal impedance‐pH system (Sandhill Scientific Inc., Highlands Ranch, CO, USA) with six impedance and two pH sensors were reviewed. An investigator was blinded to four combinations of impedance channels plus pH. He read a 3‐hour postprandial section from each of the combinations (total of 80 studies) and marked reflux episodes. Results were compared with his own interpretation of the full tracing. Two hundred and two total reflux episodes were analyzed, 113 acid (pH < 4) and 89 nonacid (pH > 4). Mean and median numbers of total reflux episodes were calculated. In the full study, the interpreter detected a mean of 10 reflux episodes per study. In the 5 cm and 7 cm, 3 cm and 7 cm, and 3 cm and 5 cm studies, the interpreter found a mean of 8.1, 11.1, and 9.8 reflux episodes per study, respectively. One‐way analysis of variance yielded a P‐value of 0.43. The trend of these preliminary findings suggests that the 3 cm and 5 cm site is the most sensitive and the 5 cm and 7 cm is the least, with the 3 cm and 7 cm site perhaps as the preferred location. The lack of a significant difference, at the very least, suggests that any of the 'mini' locations could be used. The small number of observations could have resulted in a Type II statistical error.